A compreensão da religiosidade no Psicodiagnóstico interventivo Fenomenológico-Existencial - Donatelli, Marizilda Fleury (2005)
ABSTRACT DONATELLI, MARIZILDA FLEURY: The comprehension of religiosity of clients in the Existential-Phenomenological Interventive Psychodiagnosis. PhD Thesis presented at the Post-Graduated Program in Clinical Psychology of the University Pontifícia Universidade Católica de São Paulo, Brazil: 2005. The purpose of this essay is to present a method to understand the religious conscience of the clients - children and their parents - attended in the Existential-Phenomenological Interventive Psychodiagnosis.It starts from the premise that religiosity is part of the experiences of the human beings and this is the reason why it plays a role in how people place themselves in the world, how they see the situations in their life and how they face them. To reach this objective was presented the method of evaluation of religiosity proposed by Fowler, Paloutzian and Allison, Malony and Shafranske, analyzed in the light of Fitchett standards with the intention to compare them and to extract from this comparison, elements for the selection of themes concerning religiosity to be investigated in the existential-phenomenological interventive psicodiagnosis. The method in the study of clinical case was used with thepurpose to point out the deepening of the diagnostic understanding and the enlargement of the clinical reasoning of the psychologist, thanks to the exploration of the chosen subjects in order to know more about the religiosity of the clients. I conclude that this research reveals itself as a device of utmost relevance to understand the clients, as it allows us to disintegrate certain behaviors and attitudes, to clarify premises, beliefs and values that disclose a facet, often submerged, of the experiences of human beings.